Respostas
respondido por:
54
u = (3; -1)
2u = 2 . (3; -1) = (2 . 3; 2 . (-1)) = (6; -2)
v = (-2; 4)
1/2v = 1/2 . (-2, 4) = (1/2 . (-2); 1/2 . 4) = (-1; 2)
Aplicando na equação:
3x + 2u = 1/2v + x
3x + (6; -2) = (-1; 2) + x
3x - x = (-1; 2) - (6; -2)
2x = (-1 - 6; 2 - (-2))
2x = (-7; 2 + 2)
2x = (-7; 4)
x = (-7/2; 4/2)
x = (-7/2; 2)
2u = 2 . (3; -1) = (2 . 3; 2 . (-1)) = (6; -2)
v = (-2; 4)
1/2v = 1/2 . (-2, 4) = (1/2 . (-2); 1/2 . 4) = (-1; 2)
Aplicando na equação:
3x + 2u = 1/2v + x
3x + (6; -2) = (-1; 2) + x
3x - x = (-1; 2) - (6; -2)
2x = (-1 - 6; 2 - (-2))
2x = (-7; 2 + 2)
2x = (-7; 4)
x = (-7/2; 4/2)
x = (-7/2; 2)
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás